LncRNAs as a novel source of diagnostic applications for early Alzheimer's disease and other dementia types: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Firat, Hüseyin; Nazi, Sami Ait Abbi; Bier, Jean‐Christophe; Blanc, Frédéric; Boutillier, Stéphanie; Danilin, Sabrina; David, Renaud; Démonet, Jean‐François; Dubois, Bruno; Frisoni, Giovanni B; Gabelle, Audrey; Gurvit, Hakan; et al.
Abstract: Background: There is an unmet need for an accurate, non‐invasive biomarker test for the diagnosis of early Alzheimer's disease (AD). To identify new biomarkers, we focused on long non‐coding RNAs (lncRNAs) as they are tissue‐ specific to identify lncRNA panel candidates for diagnostic of early Alzheimer's disease (AD) and other dementia types. Method: We performed a screening using NGS RNA‐Sequencing to quantify over 127000 lncRNAs in human postmortem brain tissue and blood samples including whole blood, PBMCs and, plasma samples collected in prospective clinical studies that recruited patients with early AD, patients with late AD, patients with one of the other 5 dementia types and healthy controls. Result: We identified for the first time several panels (i) a panel of brain‐enriched lncRNAs never described before, (ii) panels of brain‐enriched lncRNAs that are either expressed in whole blood or circulating in plasma. (iii) Interestingly, out of these, we also identified panels of lncRNAs that are differentially expressed in the blood of patients with AD or with other dementia types as compared to healthy control subjects. The most accurate lncRNA panel to detect early AD is selected for use as Research‐Use‐Only test and is being further validated to compile the data dossier for submission to regulatory agencies for approval as an in‐vitro diagnostic (IVD) tool diagnostic of AD. Additional clinical applications are for prognostic or theragnostic purposes. Conclusion: Our results from studies combining the use of high‐quality samples from well‐designed prospective clinical studies, cutting edge technologies and scientific knowhow enabled to translate novel brain specific lncRNA panels measurable in blood as new non‐invasive and accurate diagnostic approaches using highly specific and low represented sequences specific to neurodegenerative diseases. This project is funded by the Alzheimer's Drug Discovery Foundation (ADDF) Diagnostics Accelerator, a fund set up in collaboration with Bill Gates and other philanthropic partners, By H2020 SMEINST (GA#674474) and by EuroTransBio (ETB‐2014‐63 supported by Region Grand Est).